Benchmark for Reduction of Anchored Vessels Emissions Enabling Change of Operations - Research on air pollution management in The Port of Gothenburg, Sweden - Florez, Carlos; Betancur, Valeria (My University, 2021)
While air emission inventories can be calculated for distinct levels of accuracy depending on the availability of primary data versus average data, there are hovering assumptions in the methodologies that lead to uncertainties in assessing CO2 benchmarks for anchoring operational mode. Normally, well-grounded information is neither available for auxiliary engines nor boilers at anchor to estimate the fuel consumption and the CO2 emission that stem from it. However, research can generate primary data, as in the Brave Eco Method for tanker vessels. This case study creates a benchmark of CO2 emission for the vessel at anchor in the port of Gothenburg as well as qualitative information of energy management at anchor. The average CO2 emission rate for vessels at anchor in the port of Gothenburg was approximately 1.84 metric tonnes per hour in 2019. A similar emission rate is calculated for a period of 2021 with 1.54 metric tonnes of CO2 per hour. These emissions are calculated using a bottom-up and fuel-based inventory methodology consisting of estimating fuel consumption for all the port’s calls. Comparisons are made for world-known emission inventory methods in terms of CO2 emissions of the port calls. Spatial distributions of CO2 are shown for the designated anchor areas in Gothenburg. Ultimately, this research suggests a course of action to reduce carbon intensity in the areas adjoining the bay.
Keywords: Air emissions; bottom-up; emission inventory; port; anchor; vessel type; CO2; Maritime management